Judy Moody Gets Famous! [Dada Nálada bude slávna! anglicky] / Book 2. - McDonald, Megan 1959- (Walker Books Ltd, 2019)
Judy's in a jealous mood - jealous of Jessica Finch, who has got her picture on the front page of the newspaper. So Judy sets off in pursuit of her own fame and fortune. Judy's search for fame in sure to put you in a very Judy Moody mood.